Reconstruction with megaprosthesis for recurrent nonunion of an atypical periprosthetic femoral fracture in an elderly patient - Yuto Nishiura; Tomohiro Yoshizawa; Tomofumi Nishino; Toshiki Muramatsu; Yohei Yanagisawa; Ryunosuke Watanabe; Yasuhiro Homma (Journal of Surgical Case Reports, 2026)
Abstract An 89-year-old woman who had previously undergone cementless hemiarthroplasty for a left femoral neck fracture sustained a Vancouver type C periprosthetic femoral fracture with radiographic features suggestive of an atypical femoral fracture. Both attempts at internal fixation resulted in nonunion accompanied by plate failure. Given the well-fixed stem and the anticipated difficulty of stem extraction owing to severe proximal femoral cortical thinning, we elected to perform megaprosthetic reconstruction. Immediate full weight-bearing was permitted postoperatively, and the patient was discharged home seven weeks after surgery. In elderly patients in whom osseous union is improbable and preservation of functional independence through early weight-bearing is paramount, megaprosthetic reconstruction represents a viable salvage option.